Preface: Communicating, Educating, Interfacing during COVID-19 Pandemic - Daniele, Franca (European Scientific Journal, ESJ, 2021)
This Special Edition of the European Scientific Journal - ESJ results from the speeches that were held at the online Multidisciplinary Conference on May 17. The Conference had several Special Sessions and I had the honor to chair the session on Medical and Health communication, especially during a pandemic.